The Relation of Working Discipline and Employee Performance - Dehotman, Khornelis (International Journal of Applied Management and Business, 2023)
This paper seeks to determine the effect of work discipline on employee performance in the office staff of the Air Tiris Sub-district Head, Kampar Regency. Methodology/approach – The research was conducted at the Air Tiris sub-district office, Kampar Regency. This study uses simple linear regression with a sample of 31 employees and data collection using questionnaires and documentation. Hypotheses and data calculate use SPSS versi 25. Findings – Based on the results of the study, it was found that work discipline has a positive effect on employee performance at PT Mitra Dana Putra Utama Finance Pekanbaru. This is reflected in the t-value of 5.869 with a significance of 0.000 and t-table of 2.021, which means t-count > t-table. The influence of work discipline on employee performance is 48.2%, while the remaining 51.8% is influenced by other factors.